2017
DOI: 10.1007/s11255-017-1605-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis is associated with higher serum FGF23 level when compared with peritoneal dialysis

Abstract: These findings demonstrate that FGF23 levels are significantly higher in hemodialysis patients than that in peritoneal dialysis patients. We demonstrate an important association between dialysis modality (HD vs CAPD) and higher FGF23, independent of classical determinants (serum calcium and phosphate level).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…20 Previous studies have shown that FGF23 expression positively correlates with serum concentrations of phosphate and calcium in patients undergoing HD or PD. [21][22][23] The present findings are consistent with those of previous studies, showing that serum phosphorus is an independent predictor of FGF23 concentration, which can be explained by that high phosphorus concentrations affecting the secretion of FGF23. 5 In addition to its effects on CKD-MBD, FGF23 has been linked to iron metabolism, erythrocyte production and differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…20 Previous studies have shown that FGF23 expression positively correlates with serum concentrations of phosphate and calcium in patients undergoing HD or PD. [21][22][23] The present findings are consistent with those of previous studies, showing that serum phosphorus is an independent predictor of FGF23 concentration, which can be explained by that high phosphorus concentrations affecting the secretion of FGF23. 5 In addition to its effects on CKD-MBD, FGF23 has been linked to iron metabolism, erythrocyte production and differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, it has been shown that hemodialysis is associated with higher serum FGF-23 levels when compared with PD. [32] It is thought that the lower removal of FGF-23 causes the higher levels in hemodialysis. In fact, our group has previously shown increased levels of FGF-23 in the dialysis fluid after a 4-hour dwell in six patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor 23 (FGF23) is a bone-derived hormone that regulates renal phosphate reabsorption and vitamin D synthesis in renal proximal tubules [1]. Importantly, FGF23 levels start increasing early in the course of chronic kidney disease (CKD) and reach extremely high levels in patients on dialysis [2][3][4][5]. Serum phosphate (iP), calcium, and intact parathyroid hormone (iPTH) are proposed to regulate FGF23 levels in uremic patients on maintenance hemodialysis [6], and current data suggest higher circulating levels of FGF23 are associated with mortality [7][8][9][10][11], especially cardiovascular mortality [10,[12][13][14][15] due to vascular calcification [16][17][18][19] or left ventricular hypertrophy (LVH) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%